Introdução a álgebra no ensino fundamental: o “X” da questão - Silva, Cristiane Barcella [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Despite occupying a considerable part of the Brazilian Elementary and High School Curriculum, Algebra has been the great villain in Mathematics teaching. The results of the National System of Basic Education Evaluation (SAEB) show that rarely items related to Algebra reach a success rate of 40 percent in many Brazilian regions.The students complaints often involve exercises containing variables and unknown constants, always questioning why to mix “numbers” with “letters”. The aim of this work is to collaborate with Mathematics teachers, mainly of primary education who teach at seventh year, when traditionally the Algebra is introduced in Brazil. Our first step was prepair a survey of theoretical references that allowed us to understand the difficulties associated with Algebra teaching. After we developed a study of the different conceptions of Algebra, according Usiskin (1995) and National Curriculum Parameters (PCN 1998), seeking a better understanding of the several uses for the “letters” in this study area. This scenario allowed us to identify one of the main problems in Algebra teaching that is to become significant for the studentes the algebraic language, leading us to explore the possibilities and benefits of introducing the Algebra through the exploration of patterns and regularities. Such exploration aims to promote the development of algebraic thinking, the ability to generalize and the understanding of algebraic language. As a final result we suggested a didatic sequence composed by activities developed from some regularities patterns that can help the teacher in the algebra introduction and assist students at the development of algebraic thinking and language.

Apesar de ocupar parte considerável do currículo escolar do Ensino Fundamental e Médio, a Álgebra tem sido a grande vilã no Ensino da Matemática. Os resultados do Sistema Nacional de Avaliação da Educação Básica (SAEB) mostram que raramente os itens referentes a Álgebra atingem um índice de 40% de acerto em muitas regiões do Brasil. É frequente a reclamação dos alunos diante de exercícios nos quais as variáveis e as incógnitas se fazem presentes, sempre questionando o porquê de misturar números com letras. O objetivo desse trabalho é colaborar com os professores de Matemática, principalmente do Ensino Fundamental, em especial aqueles que lecionam nos 7º anos, momento em que tradicionalmente se dá a introdução da Álgebra no Brasil. Nosso primeiro passo no desenvolvimento desse trabalho consistiu no levantamento de referenciais teóricos, através dos quais buscamos entender as dificuldades encontradas no ensino da Álgebra. Na sequência, realizamos um estudo sobre as diferentes concepções da Álgebra, segundo Usiskin (1995) e os PCNs (1998), permitindo uma melhor compreensão sobre os vários usos das “letras” no estudo dessa área. Este cenário nos permitiu identificar que um dos principais problemas no ensino da Álgebra está em tornar a linguagem algébrica significativa para o aluno, nos levando a explorar as possibilidades e os benefícios da sua introdução através da exploração de padrões e regularidades. Tal exploração tem como objetivo promover o desenvolvimento do pensamento algébrico, a capacidade de generalização e a compreensão da linguagem algébrica. Finalmente, como resultado apresentamos uma sugestão de sequência didática, composta de atividades elaboradas a partir de determinados padrões de regularidades, que podem auxiliar o professor na introdução da Álgebra e auxiliar o aluno no desenvolvimento do pensamento e da linguagem algébricos.
Introduction algebra in basic education: the "X" question
Keywords: Math; Activities; Patterns; Algebra teaching; Algebraic thinking; Matemática; Atividades; Padrões; Ensino; Pensamento algébrico